DIGITAL TOOLS FOR IMPLEMENTING INTERNATIONAL FINANCIAL REPORTING STANDARDS IN THE PUBLIC SECTOR OF UKRAINE - HEVLYCH, Larysa; HEVLYCH, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The lack of an integrated financial reporting system based on international standards can lead to inefficient allocation of resources, loss of trust of foreign and international donors and investors and, as a result, slowing down the processes of economic recovery after the war. The lack of a comprehensive approach to the synchronous development of digital technologies and IFRS slows down the process of reforming the public sector, creating barriers to effective management of budget resources. The purpose of the article is to study the relationship between the digitalization of accounting processes in the public sector of Ukraine and the implementation of IFRS, as well as to identify digital tools that can contribute to the optimization of the accounting system, increasing transparency and efficiency of public finance management. It is substantiated that the transition of Ukrainian budget institutions to IFRS could increase the transparency, efficiency and comparability of financial reporting, but will require rethinking the concepts of the accounting system, training qualified personnel and adapting the relevant legal framework. Digital technologies have been identified that can be used as tools to facilitate the transition by automating routine processes and reducing the labor intensity of the transition itself and accounting procedures in general. According to the results of the study, it was stated that digitalization and the transition to IFRS are interrelated processes: IFRS requires a high level of accounting automation, i.e. modern digital solutions, and digital technologies accelerate the adaptation of accounting systems to IFRS. Integration of IT solutions and IFRS increases the efficiency, transparency and investment attractiveness of the public sector. Analysis of the impact of automation on the efficiency of budget accounting will be a direction of further research.